Shadows cast by stars - Knutsson, Catherine (Atheneum Books for Young Readers, 2012)
To escape a government that needs antigens in aboriginal blood to stop a plague, sixteen-year-old Cassandra and her family flee to the Island, where she not only gets help in communicating with the spirit world, she learns she has been chosen to be their voice and instrument.